Lucy & andy neanderthal ebook - Brown, Jeffrey (Lucy & Andy Neanderthal, 2016)
From the author of the New York Times bestselling Jedi Academy books comes a hilarious graphic novel series about two young cave kids living 40,000 years ago. “Lucy & Andy are Stone Age rock stars!  I loved this book!”  —Lincoln Peirce, author of the Big Nate series    Lucy and Andy are a sister and brother who get into trouble much like any sister and brother. Only difference? Lucy and Andy live in the Stone Age! Discover their laugh-out-loud adventures as the Paleo pair take on a wandering baby sibling, bossy teens, cave paintings, and a mammoth hunt. But what will happen when they encounter a group of humans? Includes extra information about Neanderthal life that's sure to appeal to future paleontologists and science phobes alike! And don't miss Lucy and Andy's next outing,  Lucy & Andy Neanderthal: The Stone Cold Age — coming soon! A New York City Public Library Best 50 Books for Kids 2016! A Chicago Public Library Best of the Best 2016! "Jeffrey Brown returns from a galaxy far, far away to bring us a whole new slew of kid-friendly characters! Just beware of mammoth dung!" —Keith Knight, author of Jake the Fake and The Knight Life   Every kid will love to go back in time with LUCY & ANDY!" —Judd Winick, author of Hilo: The Boy Who Saved the World